Enhanced CoCoSo Method for Intuitionistic Fuzzy MAGDM and Application to Financial Risk Evaluation of High-Tech Enterprises - Liu, Huanwen (Informatica, 2024)
The continuous innovation of science and technology is the foundation for the survival and development of high-tech enterprises. In order to gain a foothold in the fierce market competition, enterprises must seize market share by developing new high-tech products tailored to the market, and obtain economic benefits for maintaining survival and development. However, to ensure the smooth progress of the development and research process, sufficient financial support is required. Fundraising is particularly important, even if the required funds are raised, its own high-risk needs to be given special attention. The financial risk evaluation of high-tech enterprises is a multiple attribute group decision making (MAGDM). Recently, the Combined Compromise Solution (CoCoSo) method has been employed to manage MAGDM issues. The intuitionistic fuzzy sets (IFSs) are used as a tool for portraying uncertain information during the financial risk evaluation of high-tech enterprises. In this paper, the intuitionistic fuzzyCoCoSo (IF-CoCoSo) method is cultivated to manage the MAGDM based on the Hamming distance and Euclid distance under IFSs. In the end, a numerical case study for financial risk evaluation of high-tech enterprises is supplied to validate the proposed method. The main contributions of this paper are outlined: (1) the CoCoSo method has been extended to IFSs; (2) Information Entropy is used to derive weight based on the Hamming distance and Euclid distanceunder IFSs.(3) the IF-CoCoSo method is founded to manage the MAGDM based on the Hamming distance and Euclid distance under IFSs; (4) a numerical case study for financial risk evaluation of high-tech enterprises and some comparative analysis is supplied to validate the proposed method.